Van der Waals heterostructures of SiC and Janus MSSe (M = Mo, W) monolayers: a first principles study. Issue 43 (7th July 2020) - Idrees, M.; Fawad, M.; Bilal, M.; Saeed, Y.; Nguyen, C.; Amin, Bin
Abstract : Using DFT calculations, we have investigated the electronic structure, Rashba effect, optical and photocatalytic performance of SiC-MSSe (M = Mo, W) van der Waals heterostructures with different stacking patterns of chalcogen atoms. Abstract : Favorable stacking patterns of two models with alternative orders of chalcogen atoms in SiC-MSSe (M = Mo, W) vdW heterostructures are investigated using density functional theory calculations. Both model-I and model-II of the SiC-MSSe (M = Mo, W) vdW heterostructures show type-II band alignment, while the spin orbit coupling effect causes considerable Rashba spin splitting. Furthermore, the plane-average electrostatic potential is also calculated to investigate the potential drops across the heterostructure and work function. The imaginary part of the dielectric function reveals that the first optical transition is dominated by excitons with high absorption in the visible region for both heterostructures. Appropriate band alignments with standard water redox potentials enable the capability of these heterostructures to dissociate water into H + /H2 and O2 /H2 O.